GAMBARAN PENGETAHUAN IBU TENTANG TAHAP PERKEMBANGAN ANAK USIA 3–5 TAHUN DI DESA MAYANGREJO KECAMATAN KALITIDU KABUPATEN BOJONEGORO TAHUN 2014 - UTAMI, WIWIK; KUSUMAWATI, YENI; Lestari, Diana Puji (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACT            Capabilities and development of children aged 3-5 years including being able to walk on tiptoe, capable toileting in place, eat, wear shoes, and wear their own clothes. Phenomena that occur in the village Mayangrejo many children aged 3-5 years who should be able to feed themselves still fed her, should be able to wear their own clothes and shoes still dressed in her mother. The purpose of the study wanted to find a picture of mothers' knowledge of developmental stages of children aged 3-5 years in the Village District of Kalitidu Mayangrejo Bojonegoro2014.            Descriptive research design with a survey approach. The population of all mothers with children aged 3-5 years in 2014 Mayangrejo village 85 respondents. Large sample of 75 respondents using non-probability purposive sampling technique. Data were collected by questionnaire, and then in the editing, coding, scoring, tabulating presented in the form of frequency tables and narrative confirmed by percentage.             The results of the study of 75 respondents in the village Mayangrejo obtained 17% (13 respondents) have good knowledge, 31% (23 respondents) knowledgeable enough, and 52% (39 respondents) are less knowledgeable.             The conclusion of this study is more than most mothers have less knowledge about the developmental stages of children aged 3-5 years. It is expected that more active mother came to posyandu, actively participates in every activity counseling and asked the health workers. Health workers can be expected to conduct outreach programs regularly about child development stages that aims to provide information to mothers Keywords: Knowledge, Mother, Child Development 3-5 years of age